2022
DOI: 10.7717/peerj.13437
|View full text |Cite
|
Sign up to set email alerts
|

Association between chronic kidney disease and mortality in patients with a confirmed COVID-19 diagnosis

Abstract: Objective To determine the association between chronic kidney disease (CKD) and mortality in persons with a confirmed coronavirus disease 2019 (COVID-19) diagnosis. Methods Cross-sectional secondary baseline study. The study population consisted of 243,065 patients confirmed to have COVID-19 during May–December 2020. Stata 16.0 was used for statistical analysis, Chi-square test was used for bivariate analysis, and Poisson regression with robust variances was used for multiple analysis. Results The prevalen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…In addition, we observed that comorbidity of CKD was a risk factor for in-patient mortality. In the study of Puicón-Suárez et al, 39 patients with CKD and COVID-19 experienced higher mortality than those without CKD also in a Latin American population. CKD causes a chronic inflammatory process that promotes a dysregulated immune response to COVID-19 infection, resulting in hyperinflammation, activation and endothelial damage 40…”
Section: Discussionmentioning
confidence: 90%
“…In addition, we observed that comorbidity of CKD was a risk factor for in-patient mortality. In the study of Puicón-Suárez et al, 39 patients with CKD and COVID-19 experienced higher mortality than those without CKD also in a Latin American population. CKD causes a chronic inflammatory process that promotes a dysregulated immune response to COVID-19 infection, resulting in hyperinflammation, activation and endothelial damage 40…”
Section: Discussionmentioning
confidence: 90%
“…In addition, we observed that comorbidity of CKD was a risk factor for in-patient mortality. In the study of Puicón-Suárez et al, 39 patients with CKD and COVID-19 experienced higher mortality than those without CKD also in a Latin American population. CKD causes a chronic inflammatory process that promotes a dysregulated immune response to COVID-19 infection, resulting in hyperinflammation, activation and endothelial damage.…”
Section: Discussionmentioning
confidence: 90%
“…Moreover, DM in patients with COVID-19 infection was associated with a 0.549-fold increase in mortality 25 . Although CVD and DM were identified as high-risk factors for COVID-19 earlier than CKD, CKD had a more significant impact on mortality 14 , 26 .…”
Section: Discussionmentioning
confidence: 99%